Fabrication of titanium dioxide (TiO2) nanotube arrays doped with platin (Pt) and their photoelectrochemical characteristics - Manh, Nguyen Van; Hop, Tran Thi Thanh; Huu, Nguyen The; Tung, Ngo Trinh (Vietnam Journal of Science and Technology, 2021)
In this work, Titanium dioxide (TiO2) nanotube arrays doped with Platin (TiO2/Pt) was successfully synthesized at low temperature by anodic and chemical reduction methods. Results showed that Pt/TiO2 NTAs with 0,57 wt% Pt exhibited the highest photoelectrochemical properties. Furthermore, high surface area, small particle size and enhanced visible-light absorption as well as improved charge transfer and separation are believed to be responsible for the improvement of photocatalytic activity of the doped materials.